The Role of State Management for Independent Audit in Vietnam (International Journal of Scientific Research and Management (IJSRM), 2022)
This article aims to find out the current situation of external management for independent audit activities in Vietnam, which is mainly about the level of compliance with standards or commitments to related parties and reporting to the Securities and Exchange Commission. In addition, the article discusses the development strategy of accounting and auditing in Vietnam until 2030, including necessary activities to enhance the role of state management in independent audit activities in Vietnam